Nonlinear viscous damping and tuned mass damper design for occupant comfort in flexible tall buildings subjected to wind loading - Inaudi, José A. (2017)
During wind events, tall buildings may exhibit floor accelerations levels that compromise occupant comfort. The use of energy dissipating devices to reduce peak floor accelerations is a sound strategy to improve building performance. The estimation of mean peak floor accelerations of a steel-frame building subjected to random wind forces and the design procedure of supplemental nonlinear viscous dampers to improve occupant comfort in one-year recurrence wind events are described in this paper. A stochastic wind load model is developed to estimate acceleration performance; drag, lift and torsional moments at each story are defined as random stationary processes by the definition of their cross-spectral density matrix. Wind tunnel results and computational fluid dynamic analyses are used to fine-tune the stochastic load models. Reduced-order structural models of the tower are developed to estimate the frequency response function from floor loadings to floor accelerations at corners points of the buildings. Statistical linearization is used to estimate the performance of the buildings with non-linear viscous dampers installed in different configurations. Floor acceleration reductions achieved with supplemental viscous dampers and a tuned mass damper are evaluated to comply with occupant performance standards.